The activities of Soviet internal security agencies in Transcarpathia in 1944–1946 - Yelyzaveta Molnar D.; Molnár D. Erzsébet; Молнар Д. Єлизавета; Agoston Radvanszky; Radvánszky Ágoston; Радванскі Агоштон (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. The aim of the study is to examine how Soviet internal security organs—principally the SZMERS, NKVD/MGB and their ad hoc judicial auxiliaries—were deployed to restructure politics, society, and religious life in Transcarpathia between late 1944 and 1946. We analyse the formation and practice of extraordinary jurisdictions, the criminal-law toolkit imported from the Ukrainian SSR, and the operational methods (arrests, investigations, show trials, extrajudicial violence) used to neutralize perceived opponents and consolidate Soviet power. By situating Transcarpathia within broader postwar patterns east of the Elbe, we show how “internal security” functioned as the cutting edge of annexation and regime change. Objectives of the study. The study formulates the following objectives: (1) reconstruct the legal– institutional architecture enabling repression (with special attention to the December 18, 1944 Decree No. 22 establishing the Extraordinary Court at the People’s Council of Transcarpathian Ukraine); (2) map the primary target groups and charge patterns; (3) document interactions between security organs and ordinary courts/procuracy, including the transfer of prisons under security control; (4) assess case-level outcomes for political elites and clergy; (5) interpret the security agencies’ role in elite replacement and the integration of Transcarpathia into the Soviet administrative order. Methodological approach. The article synthesizes archival records of the Transcarpathian Regional State Archive (fond and opis citations), contemporary press, juridical texts, and memoir literature from victims and clergy. Triangulating institutional decrees, indictments, and press narratives with ego-documents allows us to differentiate constructed (fictitious-fact) from tendentious (rule-abusing) show trials—both present in the region—and to relate legal form to coercive practice. This mixed evidentiary base supports both a structural account of institutions and a prosopography of targeted groups. Scientific novelty. First, we offer a focused reconstruction of the Extraordinary Court as an instrument of internal security rather than justice, led by a politically credentialed but legally untrained chairman (Vasyl Rusyn), and positioned as a special collegium of the Supreme People’s Court—thereby formalizing security priorities in a judicial idiom. Second, we show how the swift extension (January 25, 1946) of the Ukrainian SSR Criminal Code—especially §54 (the analogue of RSFSR §58)—standardized the repertoire of “counterrevolutionary” charges (treason, armed uprising, anti-Soviet agitation, etc.) and routinized mass sentencing. Third, we link the institutionalization of security control over carceral facilities to the downgrading of the procuracy and courts to mere “order maintenance,” reframing adjudication as the execution of security decisions.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: NKVD/MGB; Extraordinary Court; Decree No. 22 (1944); §54 USSSR Criminal Code